Immune conversations at the border: meningeal immunity in health and disease - Patel, Preya U.; Regmi, Aryan; Dass, Angelina I.; Rojas, Olga L. (Frontiers in Immunology, 2025)
The brain and spinal cord, collectively known as the central nervous system, are encapsulated by an overlapping series of membranes known as the meninges. Once considered primarily a physical barrier for central nervous system protection, the bordering meninges are now recognized as highly immunologically active. The meninges host diverse resident immune cells and serve as a critical interface with peripheral immunity, playing multifaceted roles in maintaining central nervous system homeostasis, responding to pathogenic threats, and neurological disorders. This review summarizes recent advancements in our understanding of meningeal immunity including its structural composition, physiological functions, and role in health and disease.